(untitled) (Asian Journal of Social Science Studies, 2018)
This paper presents how mathematical ideas can be used to go deeply into the study of verbal cognition. Researchers in human psychology do not have an answer to the question on similarity in mechanisms of mathematical and verbal reasoning in human. The arithmetic reasoning captures deeply important properties of the world which human brain represents also in verbal cognition. Analysis of the properties of verbal thinking in comparation with mathematical cognition is an important topic in applied linguistics and cognitive psychology.